The Study of Thai Ghost Film Genre from Mae Nak - Sanchai, Patchanee (DEC Journal : Art and Design, 2023)
"The Study of Thai Ghost Film Genre from Mae Nak" The purpose is to study the form of Thai ghost film genre, which is the legend of Thai ghost film, and to study the perspective of repeated stories. 33 versions, not original version, but version made through the conceptual design process such as reinterpretation. Add roles and change perspectives. Each copy failed. Only 3 versions succeeded. "National Film Heritage" is the first Thai film "Pee Mak... Phra Khangong" with an income of 1 billion baht in 2013. It is to use the method of changing the title to tell the story from a new perspective, reduction, extention, modification and in keeping with the main plot of the film, but in a way that overturns audience expectations. 2. Nang Nak, 1999, the first Thai film to earn revenue. The highlight of THB 100 million is the new character design of Nang Nak (short hair with wearing a stripe), which highlight the authenticity and production design of the performance in the film. 3. Mae Nak Phra Khanong, 1959 the first 16mm thai film with an income of 1 million baht was reproduced through the film media with overacting. Communicate the fun in the form of folk culture in the central region. Mae Nak's Thai ghost film genre uses the same horror, comedy and romantic drama. In 2013 and 1959, since 1999 it uses horror realism.